G350(P) A national review of trainee experiences of level one paediatric training. (24th May 2017) - Galloway, L; James, D
Abstract : Aims: To evaluate current patterns of level one training, and to obtain feedback on training experiences, thereby guiding improvement to paediatric training in the UK. Methods: Heads of Schools completed a questionnaire on the format of level one training in their region. ST4–5 trainees completed a survey assessing retrospective experiences of level one training. This included value of current training models, opinion on integrating Community and Adolescent Mental Health Services (CAMHS), Primary care and Public health into training, and experiences of transition to middle grade. Results: 15/17 Heads of Schools responded. Nationally, trainees spend variable time (6–24 months) in general paediatrics. The majority spend 6–12 months in each of local neonates, tertiary neonates, and subspecialty paediatric posts. Opportunities to undertake subspecialty posts were very variable. There were no training opportunities in Primary Care, and limited scope for CAMHS or Public Health training. 80% of deaneries offered 'step-up' posts, and in 40%, trainees spend 6–12 months working on middle grade rotas. 156 ST4–5 trainees responded. The majority felt appropriate time was spent in neonates, general and subspecialty paediatrics. However, 28% of trainees reported suboptimal time in general paediatrics to prepare them for middle grade. 23% of trainees wanted more subspecialty training. Trainees would value training in Primary Care (53%), CAMHS (82%) and Public Health (61%). 55% had worked in a step-up post; this was unanimously reported to be beneficial. 51% had worked out of hours on middle grade rotas, but only 67% felt wholly supported in this role. Overall 81% of trainees felt their training prepared them for working as a registrar. Adequate consultant support, clinic exposure, pastoral and psychological input positively contributed to training experience and to the transition process. Unfortunately, service provision demands were often detrimental to training opportunities. Conclusions: Current national patterns of level one training are variable. Trainees would value time spent in Primary Care, CAMHS and Public Health training, but not at the cost of cutting general paediatric training. 'Step-up' posts, among other factors, aid smooth transition to working as a registrar. The shape of training in the future should reflect these important findings.